Epidemiological changes of Mycoplasma pneumoniae among children before, during, and post the COVID-19 pandemic in Henan, China, from 2017 to 2024 - Jiahui Qi; Hongwei Li; Hao Li; Zhuyuan Wang; Shuo Zhang; Xiangying Meng; Xin Zhao; Enwu Yuan; Linlin Zhang (Microbiology Spectrum)
ABSTRACT Studies characterizing the epidemic of Mycoplasma pneumoniae (M. pneumoniae) in Henan Province are scarce. Our research investigated the epidemiological changes of M. pneumoniae and macrolide-resistant mutations of M. pneumoniae (MRMP) among children under 18 years from January 2017 to December 2024. The study was categorized into three stages based on the COVID-19 timeline (pre-pandemic, pandemic, and post-pandemic) to analyze the impact of nonpharmaceutical interventions (NPIs) on M. pneumoniae in Henan Province. Among 27,056 children, 28.36% tested positive for M. pneumoniae, with the lowest positivity rate in 2022 (12.56%) and the highest in 2023 (35.01%). The positivity rate was greatest in the 6–17 years (41.08%) and lowest in ≤1 year (12.38%). Epidemic seasons were predominantly in autumn (36.71%) and winter (23.12%). The MRMP rate increased from 36.68% in 2018 to 87.16% in 2023, averaging 71.00%. The positivity rate of M. pneumoniae was 26.12% during the pre-pandemic stage, significantly declined during the pandemic stage (14.97%), and rebounded to a high level in the post-pandemic stage (31.88%). The MRMP rate also increased across the three stages: 46.74%, 72.63%, and 83.31%, respectively. These results indicate a significant influence of COVID-19 NPIs on the transmission of M. pneumoniae and MRMP.IMPORTANCEM. pneumoniae is a significant cause of community-acquired pneumonia with a high MRMP rate in China. Various NPIs in the COVID-19 pandemic have impacted the prevalence of M. pneumoniae and could have important implications for M. pneumoniae prevention and control strategies. Our study documented M. pneumoniae and MRMP detection before, during, and post the COVID-19 pandemic in Henan, China, from 2017 to 2024, aiming to investigate the impact of NPIs on M. pneumoniae transmission and continue to monitor the evolution of the epidemiological characteristics of M. pneumoniae infection after the pandemic when restrictive measures are no longer needed.